Airway Delivery of Bone Marrow–Derived Mesenchymal Stem Cells Reverses Bronchopulmonary Dysplasia Superimposed with Acute Respiratory Distress Syndrome in an Infant. (13th June 2018) - Lin, Hsin-Chia; Wang, Ching-Chia; Chou, Heng-Wen; Wu, En-Ting; Lu, Frank Leigh; Ko, Bor-Sheng; Yao, Ming; Wang, Po-Yuan; Wu, Mei-Hwan; Chen, Yih-Sharng
Bronchopulmonary dysplasia (BPD), a disease affecting extremely premature infants, results from the disruption of normal pulmonary vascular and alveolar growth. Currently, there is no specific effective treatment. We report a case of a 10-mo-old female infant with BPD, who was admitted because of adenovirus pneumonia and acute respiratory distress syndrome (ARDS) with prolonged venovenous and arteriovenous extracorporeal membrane oxygenation (ECMO) support (total 125 d). The respiratory condition dramatically improved, and ECMO was removed 25 d after intratracheal delivery of maternal bone marrow-derived mesenchymal stem cells (BM-MSCs). Short tandem repeat examinations revealed that there was no maternal cells in the bronchial wash fluid. To our knowledge, this is the first human report of BM-MSC therapy reversal of the course of BPD superimposed with ARDS. We also suggest that BM-MSC therapy may not only be effective in the newborn stage but also works in infants and children with BPD.